2008
DOI: 10.1167/iovs.07-1000
|View full text |Cite
|
Sign up to set email alerts
|

Macular Thickness Assessment in Healthy Eyes Based on Ethnicity Using Stratus OCT Optical Coherence Tomography

Abstract: The fovea is significantly less thick in African Americans and females than in Caucasians and males. Racial and sexual differences should be considered when interpreting an OCT scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
134
3
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(172 citation statements)
references
References 22 publications
19
134
3
12
Order By: Relevance
“…Kelty (2008) suggested thinner retinas in older patients, women, African-Americans and individuals with myopia of -5.00 dioptries or more.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kelty (2008) suggested thinner retinas in older patients, women, African-Americans and individuals with myopia of -5.00 dioptries or more.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies suggested that, in order to compare retinal thickness, it is necessary to consider gender, since their results showed thickness values significantly greater in men (8)(9) . Kelty (2008) suggested thinner retinas in older patients, women, African-Americans and individuals with myopia of -5.00 dioptries or more.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that men have thicker retinas than women (Browning et al, 2008;Guedes et al, 2003;Hee et al, 1995;Kelty et al, 2008;Massin et al, 2002;Ooto et al, 2010). However, Chan and coauthors and Grover and coauthors did not detect significant inter-sex difference in retinal thickness, but their studied groups had uneven sex distribution (Chan et al, 2006;Grover et al, 2010).…”
Section: Oct Interpretation -Quantitative Analysismentioning
confidence: 96%
“…It has been reported that Blacks and Asians have thinner retinas compared with whites in age-matched groups (Asenfzadeh et al, 2007;Guedes et al, 2003;Kelty et al, 2008). Thus, race may be taken into consideration while interpreting OCT thickness measurements.…”
Section: Oct Interpretation -Quantitative Analysismentioning
confidence: 99%